АРДЧИЛЛЫН ТАЛААРХ ҮЗЭЛ БАРИМТЛАЛЫН ХАНДЛАГУУД - Д. Бумдарь (Politology, 2023)
The field of democratic theory can be divided into two subfields: descriptive and normative theory. The role of descriptive democratic theory is to characterize and study certain features of political systems that are considered democratic